Respiratory quotient: innovative method for monitoring ‘Royal Gala’ apple storage in a dynamic controlled atmosphere (Scientia Agricola, 2015)
Apples (Malus domestica, Borkh.) which are not stored at low temperature or in a properly controlled atmosphere (CA) may have a high metabolic rate during the postharvest stage resulting in losses in quality. The aim of this study was to evaluate the quality of ‘Royal Gala’ apple fruit stored in accordance with a new method of dynamic controlled atmosphere (DCA).The respiratory quotient (RQ) was monitored at two temperatures which were then compared using a commercially available technology based on chlorophyll fluorescence DCA (DCA-CF) and static CA. Ethylene production and respiration rates were lower in apples stored in DCA than in CA, as a result of lower 1-aminocyclopropane-1-carboxylate oxidase activity, especially in apples stored in DCA-RQ2. Flesh firmness of apples stored in DCA did not differ from those stored in CA. Apples stored at 1 °C had less flesh breakdown occurrence and a high percentage of healthy fruit. ‘Royal Gala’ stored at DCA-RQ2 had less flesh breakdown than apples stored in CA; however, the apples stored in DCA-CF did not differ from those stored in DCA-RQ2 and CA. Apples stored at the highest RQ value (6 and 4), especially at 0.5 °C, had low O2 injury occurrence after storage. However the increase in temperature to 1.0 °C, reduced the occurrence of this disorder. Therefore, storage in DCA-RQ2 at 1 °C or DCA-CF at 0.5 °C are the recommendations of preference for ensuring maintenance of quality in ‘Royal Gala’ apples after eight months of storage.